Electroactive polymer-based devices for e-textiles in biomedicine. - Carpi, F.
This paper describes the early conception and latest developments of electroactive polymer (EAP)-based sensors, actuators, electronic components, and power sources, implemented as wearable devices for smart electronic textiles (e-textiles). Such textiles, functioning as multifunctional wearable human interfaces, are today considered relevant promoters of progress and useful tools in several biomedical fields, such as biomonitoring, rehabilitation, and telemedicine. After a brief outline on ongoing research and the first products on e-textiles under commercial development, this paper presents the most highly performing EAP-based devices developed by our lab and other research groups for sensing, actuation, electronics, and energy generation/storage, with reference to their already demonstrated or potential applicability to electronic textiles
Keywords: Biomedicine; Biomonitoring; Electro active polymer-based sensor; Electroactive polymer based actuator; Electronic textile; Polymer batteries; Polymer electronics; Rehabilitation; Telemedicine; Wearable man-machine interface